Spectrum of urolith composition among a multi-ethnic population at the Aga Khan hospital, Dar-es-Salaam, Tanzania - Mapendo Providence; Hussam Uddin Soomro; Natasha Housseine; Ali Akbar Zehri (PLoS ONE, 2025)
Background Urolithiasis is among the commonest diseases affecting the urinary tract with worldwide prevalence varying from 1%−20%. A urolith refers to a calculus or stone within the urinary tract, knowledge of urolith composition is important in understanding their etiology, treatment and preventing recurrence. This study aimed to describe the spectrum of urolith compositions among patients seen at the Aga Khan Hospital Dar-es-Salaam, Tanzania. Methods This was a hospital based cross-sectional study carried out among patients with urolithiasis treated during a ten-year period from January 2011 to December 2020 whose stones were sent for stone analysis by infrared spectroscopy. Data on age, sex, clinical presentation, mode of diagnosis, mode of extraction and chemical composition was analyzed. Results A total of 168 adult patients were included in the study, with a mean age of 44.7 yrs. (SD 10.99). Males (83.3%) were more affected than females. The majority (58.3%) of stones were found in the ureters. Purely calcium oxalate stones was the predominant composition of urinary tract stones, found in 66.1% of patients, this predominance was observed across both genders and across all age groups and anatomical locations, following calcium oxalate only stones in prevalence were stones with mixed calcium oxalate and calcium phosphate (21.4%). Conclusion Stones in our setting were of mixed composition. The most common constituent of stones across all ages, gender and locations was calcium oxalate only stones. Male gender was most predominant and the commonest site of urinary calculi was the ureters.